A Rare Case of Left Anterior Descending Coronary Artery to Pulmonary Trunk Fistula Associated with Takotsubo Cardiomyopathy - Ramona Mihaela Popa; Alexandru Florin Ispas; Rosana Mihaela Manea (Diagnostics, 2023)
Coronary-artery-to-pulmonary-artery fistulae represent rare vascular anomalies defined as abnormal communications between the coronary arteries and the pulmonary arterial system. Takotsubo Syndrome represents a stress-induced cardiomyopathy defined by transient regional systolic dysfunction of the left ventricle, with minimal elevation of cardiac biomarkers, without angiographic evidence of obstructive coronary artery disease. We hereby richly illustrate an unusual and rare case of a female patient with Takotsubo Cardiomyopathy and left-anterior-descending-coronary-artery-to-pulmonary-trunk fistula through multi-modality imaging evaluations, obtaining a detailed anatomical representation of the coronary arteries and the fistulous connection, which further guided the optimal treatment strategy. The patient was treated conservatively. The main teaching points of this case are the following: (1) The coronary fistula may represent just an incidental finding in a Takotsubo Cardiomyopathy clinical scenario. (2) The particularly rare association between left-anterior-descending-coronary-artery-to-pulmonary-trunk fistula and Takotsubo Cardiomyopathy presentation is mainly due to the stress-induced overstimulation of myocardial beta-1 receptors, accentuating the coronary steal phenomenon in the setting of the coronary fistula, manifesting as anginal pain, and also the stress-induced adrenergic drive causing the Takotsubo-like presentation with apical ballooning of the left ventricle.